Phosphate-selective fluorescent sensing microspheres based on uranyl salophene ionophores - Wygladacz, K.; Qin, Y.; Wroblewski, W.; Bakker, Eric (Elsevier BV, 2008)
Optical dihydrogen phosphate-selective sensors that function on the basis of bulk optode principles and are based on two different uranyl salophene ionophores are reported here for the first time. The influence of the optode composition and measuring conditions such as sample pH on the optode response are characterized, along with sensor selectivity and long-term stability. Three plasticizers of different polarity are considered for optode fabrication: bis(2-ethylhexyl)sebacate (DOS), dodecyl 2-nitrophenyl ether (o-NPDDE), o-nitrophenyloctylether (o-NPOE). The compounds 9-(diethylamino)-5-(octadecanoylimino)-5H-benzo[a]phenoxazine (ETH 5294, chromoionophore I) and 9-(diethylamino)-5-[(2-octyldecyl)imino]benzo[a]phenoxazine (ETH 5350, chromoionophore III) are used as H+-selective fluoroionophores that also act as reference ionophores. The resulting optode-based sensors are compared with their ion-selective electrode (ISE) counterparts, and it is revealed that optodes are better suited for operation at physiological pH. The best optode performance was found for the two component optode sensors doped with ETH 5350 and phosphate ionophore(I). The linear range of these sensor was log a = −6.0 to −2.6. Dihydrogen phosphate-selective optode sensors of optimized composition are fabricated in microsphere format and preliminary measurements in diluted sheep blood samples are presented.